Evaluation of Alloy Composition of A Brand of Stainless Steel K-Files (Medical Forum Monthly, 2022)
Objective: The purpose of this experimental study was to determine the alloy composition of a brand of handheld stainless steel K files, acquired from different countries, in accordance with available standards.Study Design: Comparative study.Place and Duration of Study: This study was conducted at the Institute of Space & Technology (IST) Islamabad from November 2021 to March 2022.Materials and Methods: 20 Mani stainless-steel K files of identical size (ISO#25), were acquired from Pakistan and were designated as Group A while 20 Mani K files were purchased from London, UK and designated as Group B. Alloy composition of both the sets of files was evaluated using energy dispersive X-ray spectroscopy. Data was statistically analyzed by independent sample T test and compared with American Iron and Steel Institute types 304 and 316.Results: No significant difference was found between the two groups. Nickel and chromium contents of both the groups fell within AISI 304 but content of nickel in the alloy was found to be in the lower applicable range of the specified limit.Conclusion: The results of this study indicate towards a general inclination of manufacturers towards using the lower applicable range of expensive alloying elements.